Behavioral compensation buffers body temperatures of two Liolaemus lizards under contrasting environments from the temperate Pampas: a Bogert effect?. Issue 4 (4th July 2018) - Stellatelli, Oscar A.; Block, Carolina; Villalba, Agustina; Vega, Laura E.; Dajil, Juan E.; Cruz, Félix B.
Abstract : Postural adjustments and microhabitat selection are two behavioral mechanisms that lizards extensively use to regulate their body temperatures. The Bogert effect occurs when behavioral thermoregulation buffers potential changes in body temperatures of congeneric organisms due to environmental variation, in turn precluding physiological evolution. We compared field body temperatures ( T b) and behavioral thermoregulation traits between two Liolaemus lizards: the saxicolous Liolaemus tandiliensis and the arenicolous Liolaemus wiegmannii . These species are spatially segregated in two thermally contrasting environments from the SE of the temperate Pampas of Argentina. During summer, the mean operative temperature ( T e) of the coastal sand dunes occupied by L. wiegmannii was 9 ºC higher than that of the Tandilia mountains inhabited by L. tandiliensis . Despite the contrasting thermal conditions of both habitats, the mean T b of L. tandiliensis (34.72 °C) was similar to that of L. wiegmannii (35.01 °C). The behavioral thermoregulation mechanisms varied considerably between both species. Liolaemus tandiliensis combined static body posture with displacements towards sunlit areas. In contrast, L. wiegmannii combined elevated and prostrated body postures with movements towards full and filtered sun patches. Environmental gradients offer diverse challenges impelling lizards to find different behavioral thermoregulation adaptations in order to partially cope with environmental constraints. This occurs in many species of Liolaemus that are thermoregulatory efficient despite of the climatic adversities. In this study, two species of Liolaemus used different postural and microhabitat path-selection strategies according to climate, allowing them to buffer changes in T b, thus suggesting that the Bogert effect may be occurring in these two species.